Pengaruh Kompetensi, Profesinalisme dan Perilaku Auditor Terhadap Pemanfaatan Teknologi Artificial Intelligence (AI) dan Efektivitas Pelaksanaan Audit : (Laporan Keuangan Pada Auditor Kantor Akuntan Publik (KAP) di Kota Surabaya) - Gusti Chania Raafi Iradati; Tri Ratnawati (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to investigate the influence of competence, professionalism, and auditor behavior on the utilization of Artificial Intelligence (AI) technology and the effectiveness of financial audit implementation among auditors in Public Accounting Firms (KAP) in Surabaya. The research seeks to explore how these aspects interact and impact the quality of audits. The study was conducted at Public Accounting Firms in Surabaya, with a sample of 60 auditors. Hypothesis testing in the research employed analysis using the SmartPLS 3.0 application, incorporating outer model and inner model tests. This research is expected to make a significant contribution to the accounting and audit literature by exploring the dynamics between human and technological factors in the context of financial audit. Furthermore, the results of this study can serve as a foundation for Public Accounting Firms (KAP) and regulators to design policies and training programs that support the more effective integration of AI technology into audit practices.